If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + 6 = 6 Reorder the terms: 6 + 13y = 6 Add '-6' to each side of the equation. 6 + -6 + 13y = 6 + -6 Combine like terms: 6 + -6 = 0 0 + 13y = 6 + -6 13y = 6 + -6 Combine like terms: 6 + -6 = 0 13y = 0 Solving 13y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '13'. y = 0 Simplifying y = 0
| 5m-2=4m | | 12x-39=23x-27 | | p+3=7p-35 | | .67k-5=.5k-3 | | 6h+18=2.4h+22 | | 6p+-12=-4+18 | | 6p-12=-4+8 | | -(8m+4)=4m-2(6m*2) | | x^2-60x+2500=0 | | 3x-5+x-9= | | 3x-5(5x-9)= | | 8nk-7mn=11m | | 4(x-2)+5(x+4)=-7 | | 7(x+1)=8x-7 | | 4(5r-7)+9(r+2)= | | 9a-12-11a+9= | | 9p-11-18p+7= | | 6y+(-8y)= | | 5(4-2x)=2(x-2) | | 15a-6a+9a+b= | | 12x^3-4x^2+2x+8=0 | | 5+y=70 | | 4x+5=3x+2 | | 4x-6=2(2x+3) | | x^4+2x^3-19x^2-8x+60=0 | | 60/60=60(5280)/60 | | x^3-2x^2-4x+12=0 | | 5z-(7x+7)=9 | | 3N+2b=c | | 4x+(-4)=-6 | | 11-8x=51-36x | | -144-7x=10x+22 |